A Comparative Review of the Incorporation of AI Technology in Accounting Education: South Africa and Zimbabwe Perspective - Queen Mpofu; Favourate Sebele-Mpofu (International Journal of Social Science and Religion (IJSSR), 2024)
The purpose of the study is to provide a comparative review of the incorporation of Artificial Intelligence (AI) in accounting education by the South African and Zimbabwean higher learning institutions. This was prompted by the fact that the extent to which AI has been integrated into education is not known with certainty. The study adopted a systematic literature review approach to systematically search and identify studies, extract, analyse and synthesise information guided by some pre-established guidelines (these could be design, year of publication or findings) or research protocol. To establish valid and reliable results, authors adopted seven steps recommended by the Cochrane Collaboration to conduct a systematic review. The paper findings revealed that the incorporation of AI in accounting education is at infancy phase. Both countries are currently developing an ethical AI framework aligned with their national policy strategies. This implies that the policy on incorporating AI in accounting education is still in motion. In addition, other issues that have hampered the incorporation of AI include the unavailability of digital infrastructure, the digital divide and the lack of educators' and students' education and training on AI technology. This paper recommends collaboration between academic institutions and industry and research institutions to integrate AI education into the curriculum and implement training and development programs to enhance educators' AI literacy.